Racial Discrimination in the Short Story Entitled “The Beautiful Thing” by Kit De Waal: A Critical Race Study - Darma Widiyaningsih, Ni Luh Sri; Ayu Widiastuti, Ni Made (Humanis; Vol 27 No 4 (2023)DO - 10.24843/JH.2023.v27.i04.p10, 2023)
This study aims to identify the racism issue and character discrimination portrayed in a short story entitled "The Beautiful Thing" by Kit De Waal . The short story was chosen as the primary data source since it illustrated fairly how the racism issue occurred with black immigrants in England. The data was obtained using the documentation method and a note-taking technique. The note-taking technique used to find a result in the form of sentences and phrases quotations from the short story. Furthermore, the data were analyzed by referring to six basic tenets of critical race theory proposed by Delgado and Stefancic (2001). This study was merely focused on linking the storyline which presents a racism issue with six basic tenets of critical race theory. The analysis showed that the short story presented a comprehensive illustration of racism that occurred specifically to black people in America. The racism encountered including verbal abuse and racial discrimination.